2011
DOI: 10.1097/mnh.0b013e328348b4aa
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ion transport by microRNAs

Abstract: The contribution of microRNAs to the regulation of ion transport has only begun to be unraveled, mostly in cardiomyocytes. Only a few studies have focused on the kidney but they strongly suggest that microRNAs could play an important role in the regulation of renal ion transport in response to variation in daily food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Recently, microRNAs (miRNAs) emerged as a major class of gene expression regulators implicated in deregulation of ion channel genes leading to channelopathies [9] . The consequence of miRNAs in fine-tuning gene expression shows that changes in the abundance of a single miRNA can affect the levels of expression of several different functional proteins [10, 11] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microRNAs (miRNAs) emerged as a major class of gene expression regulators implicated in deregulation of ion channel genes leading to channelopathies [9] . The consequence of miRNAs in fine-tuning gene expression shows that changes in the abundance of a single miRNA can affect the levels of expression of several different functional proteins [10, 11] .…”
Section: Introductionmentioning
confidence: 99%
“…We further demonstrated in vivo and in vitro that renal miR-200b (or miR-200b-3p) and miR-717 were tonicity-responsive and that their down-regulation contributed significantly to hypertonicity-induced induction of osmoregulatory transcription factor nuclear factor of activated T cell-5/osmotic response element binding protein/tonicity responsive element binding protein (Nfat5/OREBP/TonEBP) [4,8,16,19]. These findings firmly established the essential roles of miR-200b-3p and miR-717 in renal osmoregulation and homeostasis [5,14,15,44]. However, the roles of many other tonicity-responsive miRNAs, in particular those that appeared to be regulated in an opposite direction as compared with that of miR-200b-3p and miR-717 in vitro (i.e., up-regulated rather than down-regulated following the 2-h hypertonicity exposure), were largely uncharacterized and remained to be further investigated.…”
Section: Introductionmentioning
confidence: 65%
“…miRs are a class of endogenous and conserved small RNA molecules (~22 nt) that play gene regulatory roles in targeting mRNAs for cleavage or translational repression [17]. Based on the finding of the recent studies, miRs are found to have a pivotal role in the regulation of fluid and electrolyte balance [18,19]. It warrants further investigation to identify tonicity-inducible miRs and to determine their potential roles in osmoregulatory responses.…”
Section: Discussionmentioning
confidence: 99%